Arando terra e semeando vida: corpo e corporeidade de mulheres rurais - (:unkn) unknown (Universidade Federal do Amazonas - Universidade do Estado do Amazonas, 2024)
Research on gender in riverside, peasant, and rural areas has become a relevant topic in our country over the past decade. Researchers have delved into this theme, bringing to academia questions about the integration of psychology, as an area of knowledge, within this sociocultural and historical context. However, scientific production is still considered incipient, especially in the Amazon, likely due to its vast dimensions and the region’s inherent difficulties. It is crucial to recognize the multidimensionality of the experiences of Amazonian rural women workers and the possible invisibility of their labor as rural women. The objective of this research is to understand rural women's perceptions of bodily space and rural work through the lens of Maurice Merleau-Ponty’s phenomenology, with some insights from Simone de Beauvoir. This study is conducted from a qualitative perspective, using a phenomenological method in psychology. The research instruments included a phenomenological interview guided by a central question and its developments, as well as a Field Diary. The interview analysis followed Amedeo Giorgi’s phenomenological-psychological method. The participants were eight rural women residing in hamlets along the road to the Municipality of Manacapuru in the state of Amazonas. Three categories emerged as results: (1) “Amazonian-Rural-Woman,” (2) “Work: planting, harvesting, and caregiving,” and (3) “Embodiment in the rural woman.” The conclusion drawn is that Amazonian rural women perceive their bodies as a means of movement in rural labor. At the same time, they navigate two spaces in their work—domestic and rural. Amidst these realities, they fight to overcome the invisibility into which they are often cast, with community serving as the means through which their work gains recognition. From “im-possibility,” they create “possibility,” embodying a resilience often marginalized for being a woman, a farmer, a Northerner, and an Amazonian. Yet, in doing so, they become “women” in every sense that entails.
Keywords: Trabalhadoras rurais; Mulheres do campo; Corpo e mente; Fenomenologia; CIENCIAS HUMANAS: PSICOLOGIA; Mulheres rurais; Corporeidade; Corpo; Fenomenologia; Merleau-Ponty